Skills Acquired by Students in the Orthodontics Residence. Academic Year 2008-2009 - Clotilde de la Caridad Mora Pérez; Eduardo Maikel Curbeira Hernández; Amarelys Morera Pérez; Yuritza Hernández Núñez; Jorge A. Rodríguez López (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: learning assessment involves the monitoring and evaluation of students' knowledge, skills and habits as well as the action procedures they acquire along the educational process. Objective: to evaluate the skills acquired by fourth year Stomatology students in the orthodontics residence. Methods: descriptive, correlational, quantitative and qualitative investigation on the orthodontics residence in the University of Medical Sciences of Cienfuegos from September 2008 to February 2009. The universe consisted of 17 students who were enrolled in 4th year stay in different teaching scenarios. Five of their teachers and the 4th year general committee of educators were surveyed. Results: satisfactory results were observed as for skills acquisition in the orthodontics stay, but difficulties were identified in topics like Craniofacial growth and development and Bone-tooth discrepancy. Students expressed satisfaction with the learning process. The need of paying special attention to individual differences to achieve a more homogeneous group was evident. Conclusions: the difficulties found in the knowledge system and acquired skills, as stated in the program, justify the development of strategies to raise academic efficiency, considering that orthodontics is part of the knowledge system and the subjects needed to form these professionals.